2008
DOI: 10.18388/abp.2008_3077
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear trafficking of plasmid DNA is mediated by nuclear polymeric proteins lamins and actin.

Abstract: Functions of nuclear polymeric proteins such as lamin A/C and actin in transport of plasmid DNA were studied. The results show that the lamina plays an important role in plasmid DNA's entry into the cell nucleus from the cytoplasm. Selective disruption of lamin A/C led to a halt in plasmid DNA transport through the nuclear envelope. Inside the nucleus, plasmid DNA was frequently localized at sites with impaired genome integrity, such as DNA double-strand breaks (DSBs), occurring spontaneously or induced by ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…To promote the intracellular unpackaging of DNA, current approaches include sulfide-conjugated polymers that promote complex disassembly within the cytoplasm and “charge-shifting” polymers that release DNA upon polymer hydrolysis . Unpackaging of the DNA in the endosome or cytoplasm, however, is not ideal given that plasmid DNA cannot effectively diffuse in the cytoplasm , and has a cytoplasmic half-life of approximately 60 min . Recent studies have shown that total cellular DNA release correlates poorly with transfection efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…To promote the intracellular unpackaging of DNA, current approaches include sulfide-conjugated polymers that promote complex disassembly within the cytoplasm and “charge-shifting” polymers that release DNA upon polymer hydrolysis . Unpackaging of the DNA in the endosome or cytoplasm, however, is not ideal given that plasmid DNA cannot effectively diffuse in the cytoplasm , and has a cytoplasmic half-life of approximately 60 min . Recent studies have shown that total cellular DNA release correlates poorly with transfection efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of plastids in various forms, all plastids in a particular organism have common DNA, inherited from the maternal parent, showing that the nuclear genome is vital regulatory role over the plastid morphology and function [69]. Furthermore, the plastids are estimated to contain at least 1000, and possibly as many as 5000 different proteins, the vast majority of these proteins are encoded within the nucleus and their corresponding DNA sequences are believed to have migrated from the plastid genome during the course of evolution [70]. Thus, the high number of the cotton NLP proteins predicted to be sublocalized within the nucleus could possibly be explained by either duplication or transfer events from the plastids to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that all Cy3-pDNA clusters in the nuclear region were associated with the NE staining, suggesting that these clusters were, at least partially, entrapped in nuclear invaginations. Interestingly, Ondrej et al [116] observed that fluorescently labeled DNA signals, which seemed to be situated inside the nucleus were colocalizing with actin fibers and lamins. The authors concluded that the nucleus must therefore contain an actin cytoskeleton, which, to our knowledge, has never been reported.…”
Section: Nuclear Uptakementioning
confidence: 99%